Die "Pravila gramatičnye", der erste syntaktische Traktat in Rußland - Tomelleri, Vittorio S. (Specimina philologiae Slavicae, 1999)
In the present edition, an attempt is made to use a grammatical treatise known and sometimes misunderstood for more than 100 years, namely the Old Russian translation (hereinafter referred to as Pravila) of an anonymous medieval textbook of Latin syntax (Regulae congruitatum, constructiones et regimina, im hereinafter referred to as Regulae), in a particular form which is intended to facilitate both its consideration and evaluation as well as the interpretation of some not quite obvious points. On the one hand, the Latin template, its genesis, purpose, effect and dissemination will be examined and briefly described, on the other hand, the interlinear text form should not only allow the comparison with the Latin basic text, but also, above all, the restored interlinear text form in the foreground to let. detention